Perancangan Visual Identity Pada Butik E Collection Balikpapan Sebagai Media Informasi: Visual Identity Design at E Collection Boutique - Athaya Salsabila; Pranti Sayekti; Yon Ade Lose Hermanto (Lembaga Penelitian Pengembangan dan Pengabdian Kepada Masyarakat STMIK Asia Malang, 2023)
E Collection Boutique is one of the fashion brands in the city of Balikpapan. E Collection is a boutique business that has been running for more than 7 years in the fashion industry. A brand that has been around since 2015 in the E Walk mall, Balikpapan city. The E Collection boutique does not have a visual identity because the logo used is inconsistent. Therefore, it is necessary to design a visual identity for the E Collection Balikpapan boutique so that it can be well received by the public and gives a professional impression, in accordance with the image that the boutique wants to display, namely elegant and graceful. This design uses the Alina Wheeler method with five stages of conducting research, clarifying strategy, design identity, creating touchpoints, managing assets. Data collection techniques were carried out using a qualitative descriptive design method, namely searching and collecting data through reference sources in 4 ways, namely: In-depth Interviews, Indirect Observations, Questionnaires, Libraries. In this design using data analysis with the S.W.O.T method. This design produces the Boutique E Collection Logo and its application to related media such as taglines, super graphics and its application to other media. Keywords: Visual Identity, Boutique, Balikpapan.